PROTEST VOTE: MITIGATING THE IMPACT OF SINGLE CANDIDATES IN LOCAL HEAD ELECTIONS - Ramadani, Rizki; Asriati, Asriati; Wahida, Wahida (Diponegoro Law Review, 2025)
In the 2024 local head elections, voters in 37 regions face a growing trend of single candidates. While voters can express dissent, the blank box option is often viewed as a mere procedural formality, with current regulations failing to address the negative impact of single candidates. This paper examines the protest vote as a form of voter engagement and explores its potential institutionalization as a solution to the single-candidate issue in local head elections. Using a normative approach, the research combines conceptual and legislative analysis, along with a qualitative review of existing literature. The protest vote, viewed from a political participation perspective, should not be seen as anti-political, but rather as a way for voters to voice dissatisfaction with the system or political elites. Few countries officially recognize the protest vote, but this study argues for its institutionalization through four measures: 1) ensuring the right to protest votes in local head elections, 2) recognizing blank, null, or spoiled ballots as valid votes, 3) defining empty boxes as "None of The Above" (NOTA) and preventing unsuccessful single candidates from re-running, and 4) protecting and encouraging campaigns for protest votes.